Review of the spider wasp genus Episyron Schiødte, 1837 (Hymenoptera: Pompilidae) from India, with description of three new species - Anju, K.; Kumar, P. Girish; Thejass, P. (Zootaxa, 2024)
The spider wasp genus Episyron Schiødte, 1837 is reviewed, with five species recorded from various parts of India along with three new species described and illustrated from Kerala: E. keralaensis Anju, Girish Kumar & Thejass, sp. nov., E. nigrocalcarius Anju, Girish Kumar & Thejass, sp. nov., and E. rufotibius Anju, Girish Kumar & Thejass, sp. nov. Diagnosis of species occurring in India, comparisons of new species with congeners and a key to the Indian species also are provided.